PENCATATAN PENJUALAN UMKM BERDASARKAN PRINSIP AKUNTANSI DAN PERPAJAKAN DI TOMOHON - Kojongian, Chintia Angelica; O. Tanor, Linda A.; Bacilius, Aprili (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze sales recording in the MSME RM Cie’Reyni in Tomohon City based on accounting principles and tax regulations. The research background is based on findings that most MSMEs, including RM Cie’Reyni, have not implemented financial records in accordance with accounting principles and tax provisions, despite having an annual turnover exceeding IDR 500 million. This research employed a qualitative approach with a case study method, involving in-depth interviews, direct observation, and document analysis. The results show that sales recording is still performed manually, limited to daily expense and revenue entries, without proper application of accounting principles and without calculating payable taxes in accordance with Government Regulation No. 55 of 2022. The obstacles include limited accounting knowledge, lack of tax socialization, and minimal supporting resources. This study contributes to the literature on MSME financial record implementation based on accounting principles and tax regulations, and offers practical recommendations including structured recording procedures, basic accounting training, and the use of digital bookkeeping applications. These findings are expected to serve as a reference for the government, academics, and MSME actors to improve financial administration compliance and support sustainable business growth.